DAKWAH KULTURAL MENURUT PERSPEKTIF PENDIDIKAN ISLAM - H Misbahuddin Amin (Atta'dib Jurnal Pendidikan Agama Islam, 2020)
This journal discusses how cultural preaching is to the community in the Waempubbu village. This study aims to determine the role and propagation of culture according to the perspective of Islamic education and the strategies and prospects of cultural da'wah according to the perspective of Islamic education. To obtain data from the two problems above, the author uses the Field research method (field) by conducting interviews and then processing the data using qualitative methods, namely the data is processed based on theories to get clarity on the problem, both the data contained in the field and contained in the literature and data analysis techniques that the author uses with structured analysis techniques. Thus, the result obtained in the research is a da'wah strategy, in essence the propagation is carried out in an overt manner as practiced by the Prophet. However, the strategy carried out in the Waempubbu village of Amali sub-district is to combine it with daily activities, everything that is carried out contains da'wah while not contradicting Islamic law and da'wah by combining activities related to the Islamic ummah's major days such as two Islamic holidays. , the holy month of Ramadan, isra mi'raj and the birthday of the prophet Muhammad Saw. Meanwhile, the prospect of da'wah being carried out in Waempubbu village, Amali sub-district is to introduce the importance of the values of faith, morals, worship and muamalah. And the role of da'wah and its contribution is as a means of communication and change for Muslims who are lost and deviating from the teachings of Islam.Keywords: Cultural Da'wah, Islamic Sharia